Rethinking comparative cultural sociology repertoires of evaluation in France and the United States - Lamont, Michèle 1957-; Thévenot, Laurent (Cambridge University Press, 2000)
This book provides a powerful theoretical framework for understanding cross-national cultural differences. Focusing on France and America, it analyses how the people of these two different cultures mobilise national 'repertoires of evaluation' to make judgements about politics, economics, morals and aesthetics. The analysis draws on eight case studies by eleven French and American researchers who have worked together over a number of years to develop systematic comparisons between these countries. The topics are wide-ranging, comparing how individuals use the cultural tools at their disposal to answer questions such as: are races equal? What constitutes sexual harassment? What is the value of contemporary art? Should journalists be neutral? How can the defense of the environment be reconciled with economic imperatives? Moving beyond simplistic essentialist models of national character, this comparative approach offers important insights that will interest not only sociologists but also political scientists and anthropologists
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Sociology / Comparative method / Case studies; Evaluation / Cross-cultural studies; Evaluation / France / Case studies; Evaluation / United States / Case studies; Cognition and culture / France / Case studies; Cognition and culture / United States / Case studies; Kultursoziologie; Kulturvergleich; Frankreich; USA; Fallstudiensammlung